On the Security Analysis of a Hopfield Chaotic Neural Network-Based Image Encryption Algorithm. (30th July 2020) - Hu, Yingchun; Yu, Simin; Zhang, Zeqing
Abstract : In this paper, the security analysis of a color image encryption algorithm based on Hopfield chaotic neural network is given. The original chaotic image encryption algorithm includes permutation encryption and diffusion encryption. The result of cryptanalysis shows that the chaotic sequences generated by this algorithm are independent of plaintext image, and there exist equivalent permutation key and equivalent diffusion key. Therefore, according to chosen-plaintext attack, the equivalent diffusion key and the equivalent permutation key can be obtained by choosing two special plaintext images and the corresponding ciphertext images, respectively, and the plaintext image is further recovered from the ciphertext image. Theoretical analysis and numerical simulation experiment results verify the effectiveness of the analytical method. Finally, some improved suggestions for the original encryption algorithm are proposed to promote the security.